In silico structural-functional characterization of three differentially expressed resistance gene analogs identified in Dalbergia sissoo against dieback disease reveals their role in immune response regulation - Ijaz, Siddra; Ul Haq, Imran; Razzaq, Hafiza Arooj; Nasir, Bukhtawer; Ali, Hayssam M.; Kaur, Sukhwinder (Frontiers in Plant Science, 2023)
Plant immunity implicates enemy recognition, signal transduction, and defensive response against pathogens. We experimented to identify the genes that contribute resistance against dieback disease to Dalbergia sissoo, an economically important timber tree. In this study, we investigated the role of three differentially expressed genes identified in the dieback-induced transcriptome in Dalbergia sissoo. The transcriptome was probed using DOP-rtPCR analysis. The identified RGAs were in silico characterized as the contributors of disease resistance that switch on under dieback stress. Their predicted fingerprints revealed involvement in stress response. The Ds-DbRCaG-02-Rga.a, Ds-DbRCaG-04-Rga.b, and Ds-DbRCaG-06-Rga.c, showed structural homology with Transthyretin-52 domain, EAL associated YkuI_C domain, and Src homology-3 domain respectively, which are the attributes of signaling proteins possessing role in regulating immune responses in plants. Based on in-silico structural and functional characterization, their role was predicted in immune response regulation in D. sissoo.